A fluorescent nanoprobe for single bacterium tracking: functionalization of silver nanoparticles with tryptophan to probe the nanoparticle accumulation with single cell resolution. Issue 6 (9th February 2016) - Dojčilović, R.; Pajović, J. D.; Božanić, D. K.; Vodnik, V. V.; Dimitrijević-Branković, S.; Milosavljević, A. R.; Kaščàkovà, S.; Réfrégiers, M.; Djoković, V.
Abstract : DUV fluorescence imaging of E. coli cells incubated with tryptophan functionalized silver nanoparticles. Abstract : The investigation of the interaction of silver nanoparticles and live bacteria cells is of particular importance for understanding and controlling their bactericidal properties. In this study, the process of internalization of silver nanoparticles in Escherichia coli cells was followed by means of synchrotron excitation deep ultraviolet (DUV) fluorescence imaging. Antimicrobial nanostructures that can absorb and emit light in the UV region were prepared by functionalization of silver nanoparticles with tryptophan amino acid and used as environmentally sensitive fluorescent probes. The nanostructures were characterized by morphological (TEM) and spectroscopic methods (UV-vis, FTIR, XPS, and photoluminescence). The TEM images and the analyses of the UV-vis spectra suggested that the addition of tryptophan led to the formation of hybrid nanostructures with pronounced eccentricity and larger sizes with respect to that of the initial silver nanoparticles. The DUV imaging showed that it was possible to distinguish the fluorescent signal pertaining to silver–tryptophan nanostructures from the autofluorescence of the bacteria. The spatial resolution of the fluorescence images was 154 nm which was sufficient to perform analyses of the accumulation of the nanostructures within a single bacterium. The DUV imaging results imply that the tryptophan-functionalized silver nanoparticles interact with cell membranes via insertion of the amino acid into the phospholipid bilayer and enter the cells.